Laser Induced Modification of the Optical Properties of Nano-ZnO Doped PVC Films - Tagreed K. Hamad; Rahimi M. Yusop; Wasan A. Al-Taa’y; Bashar Abdullah; Emad Yousif (International Journal of Polymer Science)
The effect of continuous CO2 laser radiation on the optical properties of pure polyvinyl chloride and doped of ZnO nanoparticles with two different concentrations (10, 15%) has been investigated. All samples were prepared using casting method at room temperature. Optical properties (absorption, transmission, absorption coefficient, extinction coefficient, refractive index, and optical conductivity) of all films after CO2 laser irradiated have been studied as a function of the wavelength in the range (200–800) nm for three energies (300, 400 and 500 mJ). It has been found that the transmission, energy gap, and refractive index increase with increasing laser energy. The values of absorption, Urbach energy, absorption coefficient, extinction coefficient, and optical conductivity were decreased.